The art of convening authentic engagement in meetings, gatherings and conversations - Neal, Craig (Berrett-Koehler Publishers, 2011)
?Meetings are a waste of time? is a sentiment many of us share, which is tragic because meetings bring us together as human beings. To achieve the kind of meaning or breakthrough results most of us really yearn for when we gather, the key quality needed is authentic engagement: a genuine expression of what is true for us, and an attentive listening to what is true for others. Why it so often eludes us can be a matter of habit, distrust, lack of attention, or fear. As cofounders of Heartland Inc., Craig and Patricia Neal have led over 170 of their acclaimed Thought Leader Gatherings with leaders from over 800 diverse organizations. Their new book shares for the first time the unique and powerful Art of Convening model?developed in these gatherings and refined over six years of intensive trainings?which brings authentic engagement and meaning to any group that comes together for any purpose. Convening goes beyond facilitating. Convening creates an environment in which all voices are heard, profound exchanges take place, and transformative action results. The heart of this book is the Convening Wheel?a series of nine steps, or aspects, that bring the practices and principles needed for authentic engagement together as a whole. The book provides exercises, stories, and questions to help you master both the inner and outer dimensions of this work?because in convening, the state of the convener is equally as important as the physical preparations. Convening works in any setting and can be adapted to virtually any group process. With this book you have all the tools you need to develop this essential life and leadership skill, one that will lead to improved outcomes in your organization, community, family, and relationships.
Includes bibliographical references (pages 167-170) and index. - Print version record
Keywords: Business meetings; Meetings; Communication in organizations; Group facilitation; Social Facilitation; Réunions d'affaires; Réunions; Communication dans les organisations; Facilitation sociale; meetings; BUSINESS & ECONOMICS; Business Communication; Meetings & Presentations; Commerce; Business & Economics; Business Communication